“Alah Ka Nggoh!” Language Attitudes of Multilingual Speakers in Kluet Raya Districts - Husna, Faizatul; Armawi, Sullati (PAROLE: Journal of Linguistics and Education, 2024)
This research examines the growing interest in language attitudes over recent decades. Focusing on Kluet Raya region, this study explores the regional languages used across various sub-districts and the attitudes of residents toward them. The primary objective of this study is to analyze the geographic distribution and attitudes of local community in the Kluet Raya region toward their heritage languages. The researchers also use linguistic maps to reconstruct areas where Acehnese, Aneuk Jamee, and Kluet languages are spoken within the sub-districts in Aceh Selatan district. This study adopts a qualitative approach in an attempt to gain a comprehensive understanding of community attitudes on language diversity in the region. Twelve participants, selected through purposeful sampling to represent diverse backgrounds, participated in in-depth interviews. Findings reveal a strong positive attitude toward heritage languages, with local languages viewed as equally prestigious across the region. There is also a clear preference for bilingual education that includes both Indonesian and local languages for children in Kluet Raya.